A Longitudinal Study of Eating Rituals in Patients With Anorexia Nervosa - Calugi, Simona; Chignola, Elisa; Dalle Grave, Riccardo (Frontiers in Psychology, 2019)
Background. Eating rituals are any problematic behaviours involving food. They are usually observed in patients with anorexia nervosa, but research into these behaviours and their role in treatment outcomes is lacking. Objective. We set out to assess the presence of eating rituals in patients with anorexia nervosa treated by means of intensive enhanced cognitive behavioural therapy (ICBT-E), in addition to their change over time and role as potential predictors of treatment outcome. Materials and methods. Ninety adult female inpatients with anorexia nervosa were recruited. The Participants’ body mass index (BMI), and scores for Starvation Symptoms Inventory (SSI), Eating Disorder Examination (EDE) and Brief Symptom Inventory (BSI) were recorded, and a purpose-designed 9-item checklist of eating rituals was completed by trained dieticians during assisted eating—an integral part of the ICBT-E. The Structured Clinical Interview for DSM-IV was used at admission to identify the presence of coexisting axis I psychiatric disorders. All other tests were administered at baseline (admission), the end of treatment and 6-month follow-up. BMI, EDE and BSI were also re-administered after four weeks of treatment in order to examine how refeeding affects these variables. Results. We found a correlation at baseline between eating rituals and both general and eating-disorder psychopathology scores. Eating rituals were also associated with the presence of at least one comorbid anxiety disorder. ICBT-E treatment was associated with a significant reduction in eating rituals, as well as a significant increase in BMI and improved eating-disorder and general psychopathology. However, our most relevant finding was that neither baseline eating ritual scores nor their change during treatment was associated with either BMI or general or eating-disorder psychopathology scores taken at either the end of therapy or at 6-month follow-up. Conclusion. Neither the presence of nor change in eating rituals influence treatment outcomes in patients with anorexia nervosa.